The impact of audit partner's behavioural traits on audit staff's objectivity. - Koh, Hong Fong. (2008)
Auditors must exercise objectivity when forming their professional opinion. However, psychological studies have suggested that auditors may be affected by “self-serving bias” when rendering their professional service [Bazerman et al., 1989, 1997]. This study was conducted to affirm this social psychology finding in an audit environment.